2022
DOI: 10.3389/fphar.2022.844961
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Probiotics Combined With Traditional Chinese Medicine for Ulcerative Colitis: A Systematic Review and Meta-Analysis

Abstract: Background: The combination of probiotics and traditional Chinese medicine (TCM) is a prospective therapy for ulcerative colitis (UC), and its efficacy and safety need to be urgently evaluated.Objective: This study aims to comprehensively assess the efficacy and safety of probiotics combined with TCM for the treatment of UC.Methods: The Pubmed, EMBASE, Cochrane library, China Academic Journals (CNKI), Wan-fang database, Chinese biomedical literature service system (CBM), and Chinese Science and Technology Jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 114 publications
1
9
0
Order By: Relevance
“…Li-Zhong Decoction can improve UC by regulating GM and its metabolites. The combined treatment of probiotics and TCM can inhibit intestinal inflammation and reduce adverse events for UC ( Hu et al., 2022 ). (2) IBS: Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li-Zhong Decoction can improve UC by regulating GM and its metabolites. The combined treatment of probiotics and TCM can inhibit intestinal inflammation and reduce adverse events for UC ( Hu et al., 2022 ). (2) IBS: Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Li-Zhong Decoction can improve UC by regulating GM and its metabolites. The combined treatment of probiotics and TCM can inhibit intestinal inflammation and reduce adverse events for UC (Hu et al, 2022). ( 2) IBS: showed that Tong-Xie-Yao-Fang could reduce colonic serotonin levels and alleviate the symptoms of IBS by beneficially affecting GM.…”
Section: The Role Of Gm In the Tcm Treatment Of Diseasesmentioning
confidence: 99%
“…Thus, alternative medicines have recently attracted attention in treating UC. Inspiringly, TCMs and polysaccharides from TCMs have become promising alternative and complementary therapies for UC treatment with fewer side effects (19). Jia et al conducted frequency analysis and found that Atractylodes macrocephala Koidz.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the search for more effective new drugs has become an urgent task. TCM occupies an equally important position as Western medicine in health management and disease treatment, and even numerous of clinical cases have proven to be superior in treatment of certain diseases (53)(54)(55)(56). TCM is the natural treasure trove of compounds with a wide range of sources, a great deal of active ingredients, and the stability of structure (57).…”
Section: Intervention Effects Of Herbs or Herbal Extracts In Regulati...mentioning
confidence: 99%